Phytochemical Profiling and Antimicrobial Efficacy of Ficus racemosa Linn.: A Systematic Investigation Against Waterborne Pathogens - S. Dose, Nita; Tambatkar , G. D. (Journal of Neonatal Surgery, 2025)
Background: Waterborne diseases constitute a significant global health challenge, particularly in developing nations where microbial contamination of water resources remains prevalent. The emergence of antimicrobial resistance has intensified the need for alternative therapeutic strategies derived from natural sources. Ficus racemosa Linn., a medicinally important plant from the Moraceae family, has been extensively utilized in traditional medicine systems for treating infectious conditions. Objective: This investigation aimed to systematically evaluate the phytochemical composition and antimicrobial potential of Ficus racemosa extracts against selected waterborne pathogenic microorganisms and assess the plant's role in natural water purification. Methods: Various plant parts (roots, bark, leaves, fruits) were extracted using solvents of increasing polarity. Preliminary phytochemical screening identified major secondary metabolite classes. Antimicrobial activity was evaluated using agar diffusion and broth dilution methods against Gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis, Staphylococcus epidermidis, Streptomyces griseus), Gram-negative bacteria (Escherichia coli, Proteus vulgaris, Salmonella typhimurium, Corynebacterium diphtheriae), and fungal pathogens (Candida albicans, Monilinia fruticola, Auricularia polytricha). Water samples from sites with and without Ficus racemosa root growth were analyzed for microbial contamination levels. Results: Phytochemical analysis revealed the presence of alkaloids, flavonoids, tannins, phenolic compounds, terpenoids, saponins, and glycosides. Methanolic and ethanolic extracts demonstrated significant antimicrobial activity in a concentration-dependent manner. Extract I (methanolic) showed zones of inhibition ranging from 13.4 to 17.4 mm against Gram-positive bacteria at 100 μg/ml concentration. Against Gram-negative bacteria, inhibition zones ranged from 14.5 to 16.3 mm. Antifungal screening revealed substantial activity, with maximum inhibition observed against Auricularia polytricha (25 mm at 1000 μg/ml). Water samples containing Ficus racemosa roots exhibited a 99.7% reduction in total bacterial count (3.6×10⁵ to 1.2×10³ CFU/ml) with complete absence of coliforms. Conclusion: Ficus racemosa demonstrates considerable antimicrobial potential against waterborne pathogens, supporting its traditional therapeutic applications. The substantial reduction in microbial contamination in water bodies containing the plant's root system suggests promising applications in natural water purification strategies. These findings warrant further investigation into isolation and characterization of specific bioactive compounds and their mechanisms of action. .